A Silurian - Devonian marine platform-deltaic system in the San Rafael Block, Argentine Precordillera-Cuyania terrane: Lithofacies and provenance - Manassero, Marcelo Jorge (2009)
The San Rafael Block is included as a part of the pre-Andean region, in the southern sector of the Argentine Precordillera-Cuyania terrane, within the western Gondwana margin. The Río Seco de los Castaños Formation (Upper Silurian-Lower Devonian) is one of the major marine-siliciclastic pre-Carboniferous units, and is interpreted as a distal to proximal silty platform-deltaic system. The dominant sedimentary processes were wave and storm action and the source areas were located to the east, close to the study area. The rocks are mainly of immature arkosic sandstones showing both recycled orogen and continental block provenances. Sedimentological characteristics of conglomerate-filled channels and an organic-matter-rich bed are described. X-ray diffraction analyses of the clay minerals from the sequences show that very low-grade metamorphic conditions acted during the Early Carboniferous. Geochemical analyses indicate moderate to strong weathering, and potassium metasomatism. Zr/Sc ratios lower than 22, no important enrichments of Zr, Th/Sc ratios, high Sc and Cr concentration and the Eu-anomalies indicate a provenance from a less evolved upper continental crust. TDM ages and ε Nd are within the range of the Mesoproterozoic basement and Palaeozoic supracrustal rocks from the Precordillera-Cuyania terrane. Probable sources, tectonic setting and land-sea interactions are discussed. © The Geological Society of London 2009.